The membrane‐bound O‐acyltransferase domain‐containing 7 variant rs641738 increases inflammation and fibrosis in chronic hepatitis B. Issue 6 (28th April 2017) - Thabet, Khaled; Chan, Henry Lik Yuen; Petta, Salvatore; Mangia, Alessandra; Berg, Thomas; Boonstra, Andre; Brouwer, Willem P.; Abate, Maria Lorena; Wong, Vincent Wai‐Sun; Nazmy, Maiiada; Fischer, Janett; Liddle, Christopher; et al.
Abstract : Chronic hepatitis B (CHB) is characterized by hepatic inflammation that promotes progression to cirrhosis and predisposes to the development of hepatocellular carcinoma (HCC). Subtle interindividual genetic variation as well as viral and environmental factors interact to determine disease progression between individuals. Recently, the rs641738 membrane‐bound O‐acyltransferase domain‐containing 7 ( MBOAT7 ) polymorphism was demonstrated to influence histological liver damage in alcoholic liver disease, nonalcoholic fatty liver disease, and hepatitis C, but no data are available for CHB. We evaluated rs641738 influence on disease severity in a cohort of 1, 101 patients with CHB. Forty‐two patients underwent gene expression analysis to assess the functional consequences of rs641738 on hepatic MBOAT7 expression. The minor allele (T) of rs641738 was associated with greater inflammation (odds ratio [OR], 1.45; 95% confidence interval [CI], 1.06‐1.95; P = 0.001) and fibrosis (OR = 1.31; 95% CI, 1.19‐1.92; P = 0.01). Risk allele frequency in whites (0.43) was greater than in Chinese (0.24), translating to a larger size effect in the former. The rs641738 (T) allele was associated with lower hepatic MBOAT7 expression ( P = 0.008), and the latter was associated with serum liver enzymes and inflammation. Neither patatin‐like phospholipase domain‐containing protein 3 rs738409 nor transmembrane 6 superfamily member 2 rs58542926 polymorphisms influenced disease severity. Conclusion : In patients with CHB, MBOAT7 rs641738 influences hepatic inflammation and fibrosis stage. (Hepatology 2017;65:1840‐1850).